2003
DOI: 10.1136/jnnp.74.6.728
|View full text |Cite
|
Sign up to set email alerts
|

Aetiological diagnosis of brain abscesses and spinal infections: application of broad range bacterial polymerase chain reaction analysis

Abstract: Objective: To evaluate the usefulness of the broad range bacterial rDNA polymerase chain reaction (PCR) method combined with DNA sequencing in the aetiological diagnosis of intracranial or spinal infections in neurosurgical patients. Methods: In addition to conventional methods, the broad range bacterial PCR approach was applied to examine pus or tissue specimens from cerebral or spinal lesions in patients treated in a neurosurgical unit for a clinical or neuroradiological suspicion of bacterial brain abscess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 33 publications
1
25
0
5
Order By: Relevance
“…Bacterial 16S rRNA gene PCR often outperforms anaerobic culture in the detection of fastidious and anaerobic pathogens in brain abscess material (7,10,11). This may be explained due to the difficult and time-critical sample treatment in plating for anaerobic cultures.…”
mentioning
confidence: 99%
“…Bacterial 16S rRNA gene PCR often outperforms anaerobic culture in the detection of fastidious and anaerobic pathogens in brain abscess material (7,10,11). This may be explained due to the difficult and time-critical sample treatment in plating for anaerobic cultures.…”
mentioning
confidence: 99%
“…This may be one of the reasons why Eikenella is rarely identified or associated with spinal infections. The eubacterial PCR method represents a supplementary diagnostic tool in cases of fastidious growth bacteria, particularly if the diagnostic sampling is performed under empiric antibiotic therapy [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Brain abscess is caused by Mycoplasma hominis and are only identified by PCR. Based on this study, it was found that for patients with brain abscesses and spinal infections, the broad range bacterial rDNA PCR approach may be the only method to provide an aetiological diagnosis when the patient is receiving antimicrobial treatment, or when the causative agents are small to be detected by culture method (Kupila et al 2003). …”
Section: Pcr In the Diagnosis Of Brain Abscesses And Spinal Infectionmentioning
confidence: 99%